Observations on the urban ecology of the Neotropical stingless bee Tetragonisca angustula (Hymenoptera: Apidae: Meliponini) - Velez-Ruiz, Rita I.; Gonzalez, Victor H.; Engel, Michael S. (Journal of Melittology, 2013)
Tetragonisca angustula (Latreille) is a small, docile, cavity-nestingstingless bee that is widely distributed in the Neotropical region. This speciesis particularly abundant in disturbed environments, including humansettlements. Between August 2005 and March 2006, we located and followed duringeight months 59 nests of this species in Medellín, the second most populatedcity in Colombia. Herein, we document their foraging behavior, mortality, andincidence of predators and natural enemies. Also, to determine if higherambient temperature and light intensity in urban environments affect the dailyforaging activity of T. angustula, wecompared the daily foraging activity of bees from nests found in open areas in thecity and bees from nests from a nearby covered, forested area. Likewise, todetermine if urban nests of T. angustulaare largely undetected and undisturbed by people, we experimentally made themvisible by adding a ring color (white, red, or black) around the nest entrance tube.Our observations indicate that higher ambient temperature and light intensity inurban environments do not significantly affect the daily foraging activity of T. angustula. Nearly half of the markednests disappeared, thus suggesting that nests of T. angustula are often undetected by people in Medellín. We discussbriefly some features of the biology of T.angustula that might contribute to its success in urban environments.